Numerical Analysis of Conditions for Partial Discharge Inception in Spherical Gaseous Voids in XLPE Insulation of AC Cables at Rated Voltage and During AC, VLF and DAC Tests - Paweł Mikrut; Paweł Zydroń (Energies)
AC power cables play an important role in power systems, in the transmission and distribution of electrical energy. For this reason, to ensure high operational reliability, voltage withstand tests and diagnostic tests are performed at every stage of their technical life to determine the condition of cable insulation. Due to the large electrical capacitances of cable systems, modern testing methods use very low frequency (VLF) and damped oscillating (DAC) voltages. The research presented in the article analyzed the effect of the test voltage waveform parameters on the partial discharge (PD) inception conditions in spherical gaseous voids present in the XLPE insulation of AC cable model. Using COMSOL 6.1 and MATLAB R2021b, a coupled electro-thermal model of a 110 kV AC cable was implemented, for which the critical gaseous void dimensions were estimated and phase-resolved PD patterns were generated for the rated voltage and the VLF and DAC test voltages specified in the relevant standards. In the analyses for the rated voltage, the influence of internal temperature distribution, which causes modification of XLPE permittivity, was taken into account in the numerical cable model.